Patient-specific Root-analogue Immediate Titanium Premolar Dental Implants: Prospective Evaluation of Fifteen Patients with One-year Follow-up - AKKOYUN, EMİNE FULYA; DEMİRBAŞ, AHMET EMİN; ALKAN, BANU ARZU; Akkoyun, EMİNE FULYA; ALKAN, ALPER; GÜMÜŞ, HASAN ÖNDER; ALKAN, Banu Arzu; Alkan, Alper (My University, 2019)
Objective: This study aimed to evaluate the clinical use and outcomes of the patient-specific root-analogue immediate titanium premolar dental implants (PRIs) that are manufactured by using computer numerical control (CNC) machine.